Experiences of Parents of Pre-Adolescents Coping with Online Learning, Socialization and Navigating Critical Media Literacy (American Journal of Education and Technology, 2023)
COVID-19 school closures necessitated shifts in how students engaged in learning and connected socially. For pre-adolescents and their families, these closures added urgency to an already identified challenge for parents trying to navigate their children’s engagement with digital platforms. Researchers utilized interviews to explore parent and child experiences related to online learning and behavior. Online workshops provided parents with critical media literacy (CML) knowledge and skills for navigating media texts and platforms. This paper employed emergent design-based research methodology and interpretive qualitative case-study methods. Data from interviews, recordings, and field notes were analyzed thematically. The analyses identified that parents noted increased time spent online by their children due to COVID-19 lockdowns. They also highlighted concerns for child safety, issues connected to CML, acknowledgment of the benefit of a support community amongst parents, and parent-child conversations about online actions. This study affirmed the need for parent support regarding CML and digital tools in educational and social online environments and provided suggestions for ways to promote this type of support.